The challenges of multidisciplinary treatment of post-pandemic pain caused by the Sars-CoV-2 virus - Teixeira, Lucas (2020)
BACKGROUND AND OBJECTIVES: The International Association for the Study of Pain recommends revising the definition of pain to "An unpleasant sensory and emotional experience associated with, or similar to that associated with actual or potential tissue damage." In fact, pain is a personal experience influenced to varying degrees by biological, psychological and social factors.1 The pandemic caused by (SARS-CoV-2) exposed health professionals who were not prepared for the unprecedented challenges. Many focused on ventilators, intensive care beds, but others will remain at the forefront of pain management. The aim of this paper was to present a review of the impact of the COVID-19 pandemic on pain management, in addition to proposing an alternative to the present context, such as telerehabilitation. CONTENTS: This is an integrative review carried out on the databases: LILACS, Scielo, Pubmed, Scopus, Web of Science, PubCovid and databases dedicated to the publication of Preprints on the COVID-19 theme, such as Psyarxiv and Preprint MedRxiv. In this review we intend to highlight the cognitive, emotional and behavioral impairments related to pain during a pandemic caused by COVID-19. CONCLUSION: The pandemic context and social isolation can negatively interfere in the sensitivity responses and in the treatment of pain, either by the increase in pain events in the population, impacted by social and psychological losses or by the interruption of face-to-face care during a pandemic. At this point, we recommend a gradual advance in addressing current treatment today and propose a future roadmap to face challenges that may arise.